IMPLEMENTATION OF SEGMENTING, TARGETING, POSITIONING (STP) AND DIGITAL PROMOTION STRATEGY TO IMPROVE THE BRAND IMAGE OF BOARDING HOUSE VIDINI - Sudaryanto Sudaryanto; Anifatul Hanim (UNEJ e-Proceeding, 2022)
The purpose of this case study is to solve the problem by applying the relatively new theoretical approach of digital marketing in the boarding house Kos Muslimah Vidini in Jember Regency to improve retail service performance. The primary data was obtained from direct observation and interviews towards the owner of the boarding house. Through applications as a means of implementing digital media, a combination of STP and digital promotion, this study could improve brand performance. This research is a type of research that is qualitative in nature that produces a marketing strategic approach Keywords : digital marketing, STP, e-promotion, Esat Java, boarding house